Reconfigurable voltage source inverter for power factor correction of on-board chargers - Unni, Deepa Machadan; Rajalekshmi, Bindu Gopakumar (Institute of Advanced Engineering and Science, 2024)
The effectiveness and efficiency of battery chargers are crucial for the performance of electric vehicles. The growing demand for electric vehicles warrants the development of chargers with better power factor, low distortion for the input current and low total harmonics distortion. An in-depth investigation of different configurations of power factor correction converters with the above features reveals the need for additional circuitry with existing chargers. Hence this paper focuses on reconfiguring the existing voltage source inverter of the propulsion motor drive of electric vehicles (EVs) to obtain a power factor correction converter by a novel switching scheme. A bridgeless boost topology is chosen based on the performance analysis of different power factor correction topologies done on a MATLAB-Simulink platform. The simulation results prove that the proposed reconfigurable front end converter improves the input current drawn by the electric vehicle charger and improves the power quality with a low value for total harmonic distortion of 6.56%. A switching scheme is then developed for the voltage source inverter to reconfigure it as a bridgeless boost power factor correction converter. This scheme result in a high value of 0.75 for the component utilisation factor thus proving its effectiveness as compared to existing schemes.